2008
DOI: 10.1094/phyto-98-1-0038
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Relationships Between Disease Development and Airborne Inoculum in Unmanaged and Managed Botrytis Leaf Blight Epidemics

Abstract: Comparatively little quantitative information is available on both the spatial and temporal relationships that develop between airborne inoculum and disease intensity during the course of aerially spread epidemics. Botrytis leaf blight and Botrytis squamosa airborne inoculum were analyzed over space and time during 2 years (2002 and 2004) in a nonprotected experimental field, using a 6 x 8 lattice of quadrats of 10 x 10 m each. A similar experiment was conducted in 2004 and 2006 in a commercial field managed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 38 publications
4
45
0
Order By: Relevance
“…This was supported by the findings of Johnson and Powelson [9] who analyzed spore dispersal in grey mold of snap beans and found that disease incidence was 70% at a distance of 0.9 m from the inoculum source but it was less than 25% at a distance of 4 m. Further, it was observed that there was increase of disease intensity as well as spread of the infection with the increase in time intervals. The airborne inoculum of Botrytis leaf blight caused by Botrytis squamosa was analyzed over space and time by Carisse et al [10] who observed that lesion density varied from 0.00 to 15. The association of airborne conidia of B. cinerea with disease has been recorded in other crops, too, such as strawberry [11,12], raspberry [13], grapes [14,15] and gerbera [16].…”
Section: Resultsmentioning
confidence: 99%
“…This was supported by the findings of Johnson and Powelson [9] who analyzed spore dispersal in grey mold of snap beans and found that disease incidence was 70% at a distance of 0.9 m from the inoculum source but it was less than 25% at a distance of 4 m. Further, it was observed that there was increase of disease intensity as well as spread of the infection with the increase in time intervals. The airborne inoculum of Botrytis leaf blight caused by Botrytis squamosa was analyzed over space and time by Carisse et al [10] who observed that lesion density varied from 0.00 to 15. The association of airborne conidia of B. cinerea with disease has been recorded in other crops, too, such as strawberry [11,12], raspberry [13], grapes [14,15] and gerbera [16].…”
Section: Resultsmentioning
confidence: 99%
“…After exposure, the rods were kept at 4°C and the number of conidia was counted under a microscope at x250 magnification within 1 week. The counts were transformed into conidia per cubic meter of air sampled (4,7). Data analysis.…”
Section: Methodsmentioning
confidence: 99%
“…When A or Aj¡ is greater than 1 and b is equal to 1, the spatial pattern is aggregated, but the level of aggregation is not directly influenced by the mean. If A or A., and b are both greater than 1, the spatial pattern is considered to be aggregated, and the aggregation is directly related to the mean (7,13,14,18,24,25). The significance of the estimated parameters was determined with a t test, and goodness-of-fit was evaluated using the coefficient of determination (R^).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Allium crops, such as onion [15][16][17][18][19][20] , garlic and chives 21) . There are many reports about this pathogen infecting garlic sprouts in storage periods 1,2,5) , but fewer about the disease symptoms and damage in markets.…”
Section: Botrytis This Pathogen Can Directly Induce Diseases Ofmentioning
confidence: 99%